Raw sheep wool contamination with bisphenol A and parabens. An assessment of interregional differences - Gonkowski, Sławomir; Martin, Julia; Kadyralieva, Nariste; Aparicio, Irene; Santos, Juan Luis; Alonso, Esteban; Rytel, Liliana (The Science of the total environment, 2025)
The objective of this work is to investigate for the first time the contamination of raw wool with endocrine disruptor compounds - bisphenol A (BPA) and parabens (PBs), as well as to conduct the first biomonitoring study on long-term sheep exposure to these substances. The levels of BPA, methylparaben (MeP), ethylparaben (EtP), propylparaben (PrP) and butylparaben (BuP) were evaluated in wool samples (n = 100) from Kyrgyzstan and Poland using liquid chromatography-tandem mass spectrometry method. The highest levels were noted for BPA (range: 46.9–502 ng/g, mean 132 ± 70.5 ng/g) and MeP (range: 3.4 ng/g–71.1 ng/g, mean 19.9 ± 13.8 ng/g). Lower levels were found for EtP (range: <method quantification level (MQL) – 3.9 ng/g, mean 1.3 ± 0.7 ng/g), and levels of PrP and BuP did not exceed the MQL level in any sample. Differences in BPA, MeP and EtP levels between animals from Kyrgyzstan and Poland were noted. Some differences were also found between animals from places located close to each other in the same country. The results indicate that sheep are subject to long-term exposure to BPA and PBs, which depends on the local factors and likely negatively affect the animal's health status. This study highlights for the first time that raw natural sheep wool may be contaminated with BPA and PBs during the animal's life and, therefore, may be a potential source of human exposure to these substances. [Display omitted] •The first study on raw wool pollution with bisphenol A (BPA) and parabens (PBs)•The raw wool is contaminated mainly with BPA, MEP and EtP.•Clear macroregional and local differences in BPA and PBs levels in wool were found.•The wool is polluted with BPA and PBs during animal's life.•The natural raw wool is a potential source of human exposure to BPA and PBs.